Ibn Athaillah's Theodicy Thoughts About Ugliness - Bagus Nurwahyu Akhmad Faridatullah; Radea Yuli Ahmad Hambali; Maman Lukmanul Hakim; Yoshy Hendra Hardiyan Syah (al-Afkar, Journal For Islamic Studies, 2023)
This article discusses ibn Athaillah's philosophical thinking about the ugliness of the covid-19 case study as an implication of ugliness. Theology is a study in which it tends to question the justice and omnipotency of god. The study is based on literature review (Literature Review) in its literature review and in its descriptive and scholarly analysis of ibn Athaillah's corrupt thinking. In this study, the approach referred to is the "Multi-disciplinary" approach to the phenomenon of the covid-19 case study, the theological aspect of the concept of almighty belief and justice of the God in the covid-19 case, and the philosophical or sufis aspect of the thinking ibn Athaillah brought. Ibn Athaillah answered and discussed the corruption of the "Taj Al-‘Arus Al-Hawi Li Tahdzib Al-Nufus". The findings of this study are the covid-19 virus (evil) as an expression of God's affection for man by testing his loyal, patient, and faithful servants, although such vices are physically painful and not because God is not merciful, the Lord is not gracious and the Lord is not merciful. Behind such badness, however, became a medium and a pleasure to climb up to the God, cleanse sin, and draw men to the Lord.